Across the shaman's river: John Muir, the Tlingit stronghold, and the opening of the north - Henry, Daniel Lee, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2017)
Across the Shaman's River is the story of one of Alaska's last Native American strongholds, a Tlingit community closed off for a century until a fateful encounter between a shaman, a preacher, and John Muir. Tucked in the corner of southeast Alaska, the Tlingits had successfully warded off the Anglo influences that had swept into other corners of the territory. This tribe was viewed by European and American outsiders as the last wild tribe and a frustrating impediment to access. Missionaries and prospectors alike had widely failed to bring the Tlingit into their power. Yet, when John Muir arrived in 1879, accompanied by a fiery preacher, it only took a speech about 'brotherhood'--and some encouragement from the revered local shaman Skandoo'o--to finally transform these 'hostile heathens.' Using Muir's original journal entries, as well as historic writings of explorers juxtaposed with insights from contemporary tribal descendants, Across the Shaman's River reveals how Muir's famous canoe journey changed the course of history and had profound consequences on the region's Native Americans.--Provided by publisher.
Intro: To Tell the Story -- Prologue: Beacon -- Part One. Jil'kaat Aani -- Sojourners -- Power Plays -- Moving Heaven and Earth in Klukwan -- Eagles in the Heart -- Part Two. Dleit Aan'kaawu -- True Believers -- Crossed Paths -- Unbecoming Indians -- To'watte's Canoe -- Brotherhood -- Wilder Than -- Trampling the Shaman -- Epilogue: The Wild Line.
Keywords: Tlingit Indians -- Alaska -- Lynn Canal Region -- History -- 19th century; Tlingit Indians -- Cultural assimilation -- Alaska -- Lynn Canal Region -- History -- 19th century.; Tlingit Indians -- Missions -- Alaska -- Lynn Canal Region -- History -- 19th century; Naturalists -- Alaska -- Lynn Canal Region -- History -- 19th century; Shamans -- Alaska -- Lynn Canal Region -- History -- 19th century; Muir, John, 1838-1914 -- Travel -- Alaska -- Lynn Canal Region; Missionaries -- Alaska -- Lynn Canal Region -- History -- 19th century; Muir, John, 1838-1914 -- Diaries